Influence of the Characteristics of the Board of Directors on the Performance of Companies with Board Interlocking - Tayse Gomes (Revista de Administração da Universidade Federal de Santa Maria, 2019)
A question about the Board of Directors that has been the subject of research is a situation in which two or more companies share one or more administrators, a phenomenon known in the literature as Board Interlocking. In considering this event, the study aims to verify the influence of characteristics of the Board of Directors without the performance of the BM&FBovespa Novo Mercado companies practicing Board Interlocking. From econometric tests, the impact of the characteristics of these members on the value and corporate performance was evaluated. Of the 128 companies listed in the segment, 111 were found indirectly linked by the phenomenon, which represents 87% of the population surveyed, from which the 410 observations on the data of the characteristics of the members were collected. Data analysis was performed with the application of descriptive statistics, Mann-Whitney test, correlation and multiple linear regression – Ordinary Least Squares (OLS). The results showed that at the level of 1% for ROA, and of 5% for Tobin's Q and Market-to-value, performance averages are different for companies that have members of the Board of Directors with ages above and below the average. It was also observed that the Total Assets control variable exerted a significant positive influence on the three independent variables, and that the independent variables analyzed explain 36% of the variations in the performance indicator Q Tobin. Thus, it is concluded that the investigated characteristics of the Board of Directors influenced the performance of these companies.